A love letter to Europe : an outpouring of love and sadness from our writers, thinkers and artists.: an outpouring of love and sadness from our writers, thinkers and artists. (2019) - Cottrell Boyce, Frank; Dalrymple, William; Drabble, Margaret; Callow, Simon, 1949-; Emin, Tracey; Rowling, J. K; Johnson, Holly; Townshend, Pete; Bragg, Melvyn; Boakye, Jeffrey; Rauf, Onjali; Robinson, Tony; et al.
No abstract available